(untitled) (Sciential: Journal of Social Sciences and International Relations, 2025)
This article explores the strategic utilization of social media by ASEAN member states as an instrument of soft power in digital diplomacy. It discusses how social media platforms are leveraged to enhance international reputation, promote indigenous culture, public policy and fostering diplomatic relations. In the digital age, transformative impact of digital technologies has redefined conventional diplomacy, enabling direct interaction between nation-states and global audiences, particularly within ASEAN. Employing a qualitative methodology, this study analyses secondry resouces including government publications, academic literature, and social media platform. The results illuminate the indispensable role of social media in the digital diplomatic efforts of ASEAN states, including Indonesia, Malaysia, and Thailand. However, digital diplomacy also faces challenges posed by the proliferation of hoaxes and misinformation